The evolution of communication media in Moche culture - Blanco Rivero, José Javier (2018)
Starting from the improbability of the evolution of truth as a symbolic generalization, out of which a communication medium developed that built the conditions of possibility of a functional system for science, I intend to underline the contingency of such an evolutionary pathway by studying the Moche culture. The Moche represent a fit case study because of their elaborated and narrative-loaded pottery, which played the role of diffusion medium along the Peruvian North Coast. The study of Andean iconographic media and its potential for information production might bring to the foreground the Graphocentrism underlying in Luhmann`s theory of sociocultural evolution, thereby correcting his theoretical model. In addition, a complex ancient culture would serve to illustrate the preconditions that sociocultural evolution had to fulfill in order to set forth a science functional system. My hypothesis is that sociocultural evolution is guided by the dynamic interactions between success and diffusion media, which by conditioning each other sometimes favor differentiation and gain complexity, and some others impede those possibilities leading to evolutionary blind alleys.